Begg appliance management of a moderately crowded Angle Class 11 division 2 malocclusion - Ho H. C. W.; Dreyer C. W. (Sciendo, 1999)
A case is presented that shows Begg appliance management of an Angle Class II division 2 malocclusion. The judicious use of anchorage bends and Class II elastics enabled the successful treatment of the poor posterior and anterior relationships, at the same time addressing the chief complaint of crooked front teeth.